Pelatihan Manajemen Usaha dalam Meningkatkan Usaha UMKM di Kota Tangerang - Henry Gunawan; Astrid Amalia Noeraini; Sutandi Sutandi; Kheiline Kheiline; Yonardo Davinchi (Jurnal Informasi Pengabdian Masyarakat, 2023)
To expand the MSME network and based on existing phenomena, we aim to conduct business management training in improving businesses for MSMEs in Tangerang City. Improving businesses from various aspects such as increasing income/revenue, in addition to expanding networks, increasing promotions, improving financial management, increasing creativity. There are still many MSME actors who do not have marketing planning, marketing strategies, promotions and online sales through social media or e-commerce, lack of information about good and correct simple bookkeeping and financial management. MSME actors still combine personal money with business money. Counseling and training programs can be organized well and run smoothly according to the activity plan that has been prepared. The response from partners is very enthusiastic, this can be seen from the questions asked by partners. The material presented is also relevant to the desires and needs of partners in developing their businesses. Recommendations related to the implementation of this community service are to hold training and socialization about applications to make it easier for MSMEs to develop their businesses.